?A COMPARATIVE STUDY OF SELECTED AFRICAN EDIBLE OILS AND THEIR POTEN- TIAL DOMESTIC AND INDUSTRIAL ApPLICATIONS (Biological Sciences - PJSIR, 2000)
A comparative study on the physical and chemical characteristics. Melon seed oil (Colocynthis Citrullus L.), African oil bean oil (Penta celethra, macrophylla) and Avocado pear oil (Perse, Americana) was undertaken to assess their potential domestic and industrial applications. This study focussed on the percentage oil content, individual odour (aroma), specific gravity, refractive index, relative viscosities, smoke points, acid values, free fatty acid contents (%), iodine values, and ester values. The iodine values obtained for these oils were: 151.72 (melon seed); 113.00 (African oil bean oil); 43.30 (Avocado oil). The same oils showed free fatty acid contents as 2.38%; 0.97% and 0.37% respectively, whereas acid values recorded were 4.76 (melon); 1.65 (African oil bean oil) and 0.82 (Avocado pear oil).The saponification values were 197.56 (melon), 185.08 (African oil bean oil) and 246.70 (Avocado pear oil) and the individual Ester values were 192.81 (melon), 183.63 (African oil bean oil) and 241.50 (Avocado per oil). Melon seed, African oil bean seed and Avocado pear gave 57.40%; 42.07% and 15.13% of oil following the extraction procedures outlined in the project.The potential domes- tic and industrial applications of the oils under study have been discussed in line with their physical and chemical charac- teristics.